Love and Compassion from the Perspective of the Qur’an and Hadith as Shapers of Effective Pedagogical Relationships in Islamic Education - Muhammad Azhari; Mahyuddin Barni; Abdul Basir; Ali Muammar (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to examine in depth the concepts of love and compassion in learning from the perspectives of the Qur’an and Hadith and their relevance to contemporary pedagogical practices at SMAN Banjarbaru. The research focuses on how the values of rahmah (compassion), mahabbah (constructive love), and rifq (gentleness) are internalized in the learning process and their implications for character formation, classroom climate, and teacher–student relationships. The methodology employed is a qualitative approach with a field study design, using participant observation, in-depth interviews with teachers and students, and analysis of learning documents. The data were analyzed through thematic analysis and source triangulation to ensure the validity and reliability of the findings. The findings indicate that the implementation of love and compassion values in learning significantly contributes to increased learning motivation, psychological safety, awareness-based discipline, and the strengthening of students’ social and religious character. However, the study also reveals structural and cultural challenges, such as the dominance of cognitively oriented learning paradigms, limited teacher training in humanistic pedagogy, and academic performance pressures that hinder the internalization of spiritual values in daily learning practices. This study concludes that love and compassion should be positioned as a core paradigm in education rather than merely a methodological approach, in order to develop a humanistic, transformative learning model oriented toward the development of a progressive, ethical, and civilized society